Optimization of Environmental Cleanliness Through Preventive Measures Against Covid 19 by Self-Spraying in Cikarawang Village - Ramadhani, Dinda Silviasari; Parinduri, Siti Khodijah (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2024)
Covid-19 is a virus that attacks the respiratory system and can be transmitted through touch. To reduce the transmission of COVID-19, KKN UIKA Cikarawang Village carried out various environmental optimization activities as well as preventive activities against COVID-19. One of the activities is spraying disinfectants around the village. The method used is licensing to the village for the implementation of disinfectant spraying around the village, the next is to give a warning to residents with posters and then make disinfectants, and the last is the implementation of spraying. The last stage is evaluation, the implementation team conducts discussions with the village head regarding activities that have been carried out to prevent COVID-19 and optimize the environment in Cikarawang village. The results showed the conclusion that the community gave a positive response to this activity and hoped to make disinfectants correctly independently.